2018
DOI: 10.1016/j.scitotenv.2017.12.136
|View full text |Cite
|
Sign up to set email alerts
|

Long-term observations of the background aerosol at Cabauw, The Netherlands

Abstract: Long-term measurements of PM mass concentrations and aerosol particle size distributions from 2008 to 2015, as well as hygroscopicity measurements conducted over one year (2008-2009) at Cabauw, The Netherlands, are compiled here in order to provide a comprehensive dataset for understanding the trends and annual variabilities of the atmospheric aerosol in the region. PM concentrations have a mean value of 14.4μgm with standard deviation 2.1μgm, and exhibit an overall decreasing trend of -0.74μgmyear. The highes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
(26 reference statements)
1
6
1
Order By: Relevance
“…32%, 26% and 36%, respectively, during winter than during the summer. This observation is consistent with similar measurements from other cities reported in the literature (Carbone et al, 2010;Triantafyllou and Biskos, 2012;Perrino et al, 2014;Mamali et al, 2018), and can be attributed to i) the additional emissions from domestic heating during winter, and ii) the lower dilution associated to the weaker winds and the lower boundary layer heights (ca. 39%; i.e., average values calculated by WRF-Chem model) in winter compared to summer (cf.…”
Section: Particle Mass Concentrationssupporting
confidence: 92%
See 1 more Smart Citation
“…32%, 26% and 36%, respectively, during winter than during the summer. This observation is consistent with similar measurements from other cities reported in the literature (Carbone et al, 2010;Triantafyllou and Biskos, 2012;Perrino et al, 2014;Mamali et al, 2018), and can be attributed to i) the additional emissions from domestic heating during winter, and ii) the lower dilution associated to the weaker winds and the lower boundary layer heights (ca. 39%; i.e., average values calculated by WRF-Chem model) in winter compared to summer (cf.…”
Section: Particle Mass Concentrationssupporting
confidence: 92%
“…Although the concentrations of main air pollutants has been decreasing in large European cities during the last decade (Klimont et al, 2013;Guerreiro et al, 2014), airborne particles having sizes smaller than ca. 2.5 κm (i.e., PM 2.5 ) often exhibit values above or close to the EU annual standard (25 κg m -3 ) mainly due to the numerous and intense anthropogenic sources, including transportation, domestic combustion processes and industrial activities (Szigeti et al, 2013;Eleftheriadis et al, 2014;Manousakas et al, 2015;Diapouli et al, 2017a;Mamali et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there is some support that recent models can predict spatial variation of UFP levels for periods of 10 years moderately well. This is corroborated by the relatively small trend in particle number concentrations seen at a background measurement location in the Netherlands over a period of 8 years, from 2008 to 2015 (Mamali et al, 2018). Similarly, we used LUR models based on measurements from 2008 to 2010 for the co-pollutants.…”
Section: Two-pollutant Exposure Modelsmentioning
confidence: 71%
“…Previous studies showed that clean air masses are often received from the North Sea or Scandinavia. In contrast, polluted air masses generally originate from southern Europe (Mamali et al, 2018). Continuous observations of aerosol physiochemical properties were conducted during the RITA-2021 campaign from 11 to 24 May and from 16 September to 12 October 2021; additional measurements such as meteorological data from the 213 m high mast of Cabauw tower at 10 min time resolution were available via the KNMI Data Platform 4 .…”
Section: Site and Campaign Descriptionmentioning
confidence: 99%